OP0217 Frequent Detection of Inflammation and Fat Infiltration Suggestive of Spondyloarthritis on MRI of the Entire Spine in Healthy Subjects and Patients with Mechanical Back Pain. (23rd January 2014) - Weber, U.; Zhao, Z.; Zubler, V.; Chan, S. M.; Lambert, R. G.; Ostergaard, M.; Pedersen, S. J.; Maksymowych, W. P.
Abstract : Background: Mechanical back pain (MBP) patients and healthy subjects may show spinal MRI lesions suggestive for spondyloarthritis (SpA) such as corner inflammatory lesions (CIL) or corner fat lesions (CFL). There are few data about their frequency and whether they may result in a false positive classification of controls as having SpA. Objectives: To assess the frequency of false positive classification as SpA in controls consisting of MBP patients and healthy volunteers, and to evaluate which MRI lesion type has the highest impact on misclassification. Methods: The study sample comprised 2 independent cohorts A/B of 130 consecutive patients with back pain ≤50 years newly referred to 2 university clinics, and 20 healthy controls, in whom MRI scans of the entire spine were available. Patients were classified according to clinical examination and pelvic radiography as having non-radiographic SpA (nr-axSpA; n=50), ankylosing spondylitis (AS; n=33), or MBP (n=47). Age-matched healthy controls in cohort A were recruited according to the Nordic Questionnaire from hospital staff of the same clinic that also recruited the SpA patients. Spinal MRI were assessed by 4 blinded readers according to the Canada-Denmark MRI definitions for spinal lesions [1, 2 ]. Readers recorded bone marrow edema (BME) and fat infiltration (FI) in the central, lateral and posterior compartment of all 23 discovertebral units. The mean number (percentage) of controls misclassified as having SpA by the 4 readers and the principal spinal lesions indicative of SpA were analysed descriptively. Results: 33.9%/28.0% of MBP patients in cohorts A/B, and 26.3% of healthy subjects in cohort A were misclassified as having SpA by global assessment of MRI of the entire spine. Both BME and FI in varying percentages were the most important MRI lesions leading to this misclassification. The mean number of CIL and CFL observed in controls was lower than in SpA patients. Mean percentage of false positive controls, principal MRI lesions responsible for misclassification, and mean number for CIL and CFL on spinal MRI in cohort A/B Conclusions: 26% to 34% of healthy controls and patients with MBP were misclassified as having SpA by evaluation of MRI of the spine alone. Caution is warranted if a classification of SpA is based on MRI of the spine alone. References: Lambert R et al. J Rheumatol 2009;36 suppl 84:3. Ostergaard M et al. J Rheumatol 2009;36 suppl 84:18. Disclosure of Interest: None Declared